Analisis Nilai Toleransi Dalam Buku Bahasa Indonesia Kurikulum Merdeka Sekolah Dasar - Ngulya, Khilyatul; Sukardi, Sukardi (Jurnal keilmuan dan Kependidikan dasar, 2024)
Developing students’ positive character is important, particularly the character of tolerance to minimize cases of intolerance. This study aims to describe the form of tolerance learning contained in the Indonesian language book of the independent curriculum for grade II elementary school. The formulation of the problem is how the form of tolerance learning is contained in the Indonesian language book of the Merdeka Curriculum for Grade II Elementary School. This research is library research. Data collection techniques using reading techniques, note-taking techniques, and documentation. The data collection instrument is a human instrument. The data analysis technique uses content analysis techniques. The object of this research is the Indonesian language book for the independent curriculum for grade II elementary school by Widjati Hartiningtyas & Eni Priyanti entitled "My Family is Unique". The results showed that the form of tolerance learning can be categorized into 4, namely observing and identifying individual differences in class and family through pictures, discussing differences with friends, writing about asking permission when borrowing items, and reading fairy tales about examples of intolerant attitudes